A Brief Review on the Importance use of Solar Energy in the Treatment of Recalcitrant Effluents Applying Advanced Oxidation Processes - Queiroz, Marluce Teixeira Andrade; Sabara, Millor Godoy; Alvim, Lucas Barbosa; Queiroz, Carolina Andrade; Leão, Monica Maria Diniz; Amorim, Camila Costa (Ciência e Natura, 2015)
Several studies have reported the adverse effects of persistent compounds in the wastewater, showing the fragility of the biologic treatment. Harmful effects for both aquatic biota and human being are caused by those compounds. In order to minimize the adverse environmental impacts, Advanced Oxidation Processes (AOPs) are used in the degradation of those pollutants to achieve high removal rates. In the present the comparisons between the efficiency of AOPs using natural and artificial Ultra Violet light (UV) were made based on the literature review, addressing constructive and operational characteristics of the reactors. The findings indicated that the high levels of solar energy, which are registered in different regions of Brazil, show the viability of the AOP using natural radiation to the decontamination of industrial effluents. Thus the inclusion of advanced oxidation in the treatment of wastewater could be considered as a significant contribution to the supported development in Brazil.